PEMBENTUKAN KARAKTER PESERTA DIDIK OLEH GURU KELAS - Wasiman, Wasiman (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to examine the role of Class Teachers in the formation of character of students as well as factors that influence the role of teachers in the formation of character of students. The method used is qualitative with a phenomenological approach. The results of the study state that the role of Class Teachers as educators is realized by directing the talents and abilities of students, being responsible and realizing authority. Class Teachers as instructors are realized by planning and implementing learning. Class Teachers as role models are manifested in exemplary appearance, association, and concern for the environment. Class Teachers as trainers are realized by building awareness of students, carrying out the character taught with teachers and students.